Diel to Seasonal Variation of Picoplankton in the Tropical South China Sea - Chen, Tzong-Yueh; Lai, Chao-Chen; Tai, Jen-Hua; Ko, Chia-Ying; Shiah, Fuh-Kwo (Frontiers in Marine Science, 2021)
Eight diel surveys on picoplankton (Prochlorococcus, Synechococcus, picoeukaryotes, and heterotrophic bacteria) abundance at the SouthEast Asian Time-series Station (SEATS; 18 oN; 116 oE) have been conducted during the period of 2010 to 2014. The results indicated that Prochlorococcus and picoeukaryotes showed a subsurface maximum in warm seasons (spring, summer and fall) and were abundant at the surface in the cold season (winter). On the other hand, Synechococcus and heterotrophic bacteria exhibited higher cell numbers at the surface and decreased with depth throughout the year. Although not all, some clear diel patterns for picoplankton have been observed. Picophytoplankton usually peaked in the nighttime: picoeukaryotes peaked around 7 to 8 pm, followed by Synechococcus (peaking at 1 am) and Prochlorococcus (peaking at 2 am). Unlike these picoautotrophs, heterotrophic bacteria could peak either at dust (i.e. 7 pm) or at noon. Seasonally, Prochlorococcus was more abundant in the warm than the cold seasons, while Synechococcus and picoeukaryotes showed blooms in the winter of 2013 and 2011, respectively. Heterotrophic bacteria showed no significant seasonality. Regression analysis indicated that ~73% of the diel-to-seasonal variation of the euphotic zone depth-integrated picophytoplankton biomass (i.e. PicoBeu) could be explained by the changes of the mixed-layer depth (MLD), and this suggested that inorganic nutrient supply could be the major controlling factor on their growth. The strong relationship (coefficient of determination, R2 of 0.83) between sea surface temperature (SST) and PicoBeu implied for the first time, a potential of using satellite SST to trace the biomass of picophytoplankton in the pelagic areas of the northern South China Sea.